Freud's Psychoanalysis on the Religious Practice of Manhaj Salaf as a Psychic Mechanism in Facing Modernity in Indonesia - Elicia Eprianda (UIN Sunan Kalijaga Yogyakarta, 2025)
This paper aims to examine how the religious practice of manhaj Salaf in Indonesia can be understood through the psychoanalytic framework of Sigmund Freud. In the last two decades, the growth of this movement reflects the search for moral certainty and identity in the midst of a crisis of meaning in modernity. The formulation of this research problem includes: (1) how the structure of id, ego, and superego works in the formation of Salafi piety and moral discipline; (2) what psychic defense mechanisms appear in their religious practices; and (3) how those psychic dynamics operate in response to the uncertainty and pressures of modernity. Using a qualitative approach based on literature review, this study hypothesizes that Salafi religious practices function as a psychic mechanism to reduce existential anxiety through the formation of collective superegos, sublimation, and social projection. The results of the analysis show that the internalization of strict religious norms provides a sense of psychological security and identity stability, but also has the potential to create excessive guilt and exclusivity towards other groups. In conclusion, Freud's psychoanalysis provides a strong perspective to understand the psychological function of Salafi religiosity in the context of Indonesian modernity and opens up space for further studies of the relationship between moral obedience, psychological health, and social dynamics. Abstrak Tulisan ini bertujuan menelaah bagaimana praktik keagamaan manhaj Salaf di Indonesia dapat dipahami melalui kerangka psikoanalisis Sigmund Freud. Dalam dua dekade terakhir, pertumbuhan gerakan ini mencerminkan pencarian kepastian moral dan identitas di tengah krisis makna dalam modernitas. Rumusan masalah penelitian ini mencakup: (1) bagaimana struktur id, ego, dan superego bekerja dalam pembentukan kesalehan dan disiplin moral Salafi; (2) mekanisme pertahanan psikis apa yang muncul dalam praktik keagamaan mereka; dan (3) bagaimana dinamika psikis tersebut beroperasi sebagai respons terhadap ketidakpastian dan tekanan modernitas. Dengan menggunakan pendekatan kualitatif berbasis kajian pustaka, penelitian ini mengajukan hipotesis bahwa praktik keagamaan Salafi berfungsi sebagai mekanisme psikis untuk mereduksi kecemasan eksistensial melalui pembentukan superego kolektif, sublimasi, dan proyeksi sosial. Hasil analisis menunjukkan bahwa internalisasi norma religius yang ketat memberikan rasa aman psikologis dan stabilitas identitas, namun juga berpotensi menciptakan rasa bersalah berlebih dan eksklusivitas terhadap kelompok lain. Kesimpulannya, psikoanalisis Freud menyediakan perspektif yang kuat untuk memahami fungsi psikologis religiositas Salafi dalam konteks modernitas Indonesia serta membuka ruang bagi kajian lanjutan mengenai hubungan antara ketaatan moral, kesehatan psikologis, dan dinamika sosial.